Aplikasi Teknologi Irigasi Drip pada Produksi Bunga Hortensia di Kelompok Tani Bima, Kabupaten Banjarnegara, Jawa Tengah - Erni Sumarni; Ponendi Hidayat; Imastini Dinuriah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Bima Farmer Group of Dieng Kulon Village, Banjarnegara is a micro-enterprise in the agricultural sector and a center for exotic ornamental plants, particularly Hydrangea flowers. Hydrangea is a leading commodity within the Bima Farmer Group and supports the development of tourism in Dieng Kulon, Banjarnegara. Some of the challenges faced by the group in maintaining productivity include the topography of Banjarnegara, which has a land slope of 45.04%, posing risks to effective and efficient irrigation and fertilization technologies. This research-based community service activity aims to transfer drip irrigation technology to assist in the management of water and nutrients for Hydrangea flower production. The methods used in this technology transfer activity are as follows: 1) Providing assistance and hands-on practice in nutrient management for Hortensia flower production, 2)Establishing demonstration plots using drip irrigation technology for Hortensia flower cultivation, and 3) Conducting activity evaluations to assess the farmers group's level of understanding. Results from this activity show a significant improvement in the farmer’s understanding of the technology transfer, increasing from 3–5% to 85–87%. The average number of Hydrangea flower heads per plant per season before drip irrigation was 6–9, which increased to 11–13 flower heads per plant after implementation. Fertilization became more controlled with the use of drip irrigation, and water usage was reduced by 30–55% compared to conventional methods. Nutrient and water supply remained stable due to the drip irrigation technology. The sustainability of this technology transfer has been well received by the Bima Farmer Group, which plans to expand drip irrigation to other cultivation areas.